Investigating the relationship between joint coupling coordination and muscle activity during walking - Ong, A.; Zixing, L.; Hamill, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The study aimed to investigate the relationship between joint coupling coordination and muscle activity of the lower limb during normal gait in shod and barefoot walking. Ten healthy participants served in this study. We assessed joint coordination and muscle activity while the participants walked on a treadmill at their self-selected speed in shod and barefoot conditions. T-tests were used to determine the differences between walking conditions in the early, mid and late phases of support. A cross-correlation analysis was used to determine the similarity between the coordination angle and EMG profiles in the three phases of support. The study suggested no differences between shod and barefoot coordination. The correlation coefficients were moderately high (r=0.6) for both shod and barefoot. It was concluded that the rearfoot/tibia coordination may be under passive rather than active control.